UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK SIKAP JUJUR DAN TOLERANSI SISWA SEKOLAH MENENGAH PERTAMA NEGERI 11 KOTA JAMBI - Yoganindra, Fifky; Surayya, Ely (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study investigates the efforts of Islamic Education teachers in fostering students’ honesty and tolerance at Sekolah Menengah Pertama Negeri 11 Kota Jambi. The problem addressed in this research is the persistence of dishonest behaviors and limited tolerance among students in daily school life, indicating that character education has not been optimally implemented. The purpose of this study is to describe the forms of teachers’ practices, the obstacles encountered, and the strategies employed to strengthen students’ honest and tolerant attitudes. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews with Islamic Education teachers, classroom and school observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings show that Islamic Education teachers play a central role in cultivating honesty and tolerance through the integration of character values into learning materials, role modeling, habituation activities, and dialogical learning strategies. However, several obstacles were identified, including students’ diverse backgrounds, limited parental involvement, and inconsistent reinforcement of school rules. To address these challenges, teachers strengthen collaboration with school stakeholders and parents, improve classroom management, and continuously reinforce positive behaviors through counseling and reflective activities. Overall, the study concludes that consistent pedagogical practices, exemplary conduct, and collaborative efforts are essential to effectively develop students’ honesty and tolerance in the school environment.